A Global Perspective on Effectiveness of Aid for Trade - Berrittella, Maria; Zhang, Jian (World Bank, Washington, DC, 2012)
Recent global initiatives on debt relief and development assistance call for increasing aid for trade to the poorest countries. The paper applies a multi-country computable general equilibrium model to measure the effectiveness of alternative aid for trade categories. The findings show that aid for trade policies expand trade and alleviate international income inequalities in the recipient countries, that will benefit mainly from aid for trade adjustment and technical assistance.